Pengaruh Strategi Pemasaran dan Kualitas Layanan Terhadap Keputusan Pemilihan Sekolah: (Studi Kasus Pada Kelas X di SMK Negeri 1 Kuripan) - Sikki, Nurhaeni; Makbul, Aktris Monika Favorit; Juanda, Agus; Akhifin, Akhifin; Harahap, Linda Rahmadhani; Klarita, Endi Liani; Amalia, Anggi; Rifal, Dwiki Indar (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This research examines the influence of Marketing Strategy and Service Quality on School Selection Decisions (Case Study in Class X at SMK Negeri 1 Kuripan). This research used multiple linear regression analysis and involved a population of 133 students. The decision to choose a school is the dependent variable, while the independent variables are marketing strategy and service quality. Marketing strategy dimensions include market segmentation, market promotion, positioning, information distribution. Service quality is categorized into five dimensions: reliability, responsiveness, assurance, empathy, physical evidence. School selection decisions consist of information factors, price factors, school quality factors, and facility factors. Data collection was carried out using observation and questionnaires. Various statistical methods, such as partial hypothesis testing, simultaneous analysis, and coefficient of determination, should be used in this research. The research results show that marketing strategy partially influences school selection decisions. Service quality influences school selection decisions. marketing strategy and service quality simultaneously influence school selection decisions